Tafsir Ayat-ayat Perintah Haji dalam Konteks Ke-Indonesiaan - Lenni Lestari (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
One of the challenges being faced by Indonesia today is disparity between a number of people who will have a pilgrimage to Mecca and a number of needy families trapped below the poverty lines. It shows that re-pilgrimage’s phenomenon in Indonesia had no contribution to the social change. First, this article tries to discuss and analyze the position of re-pilgrimage in Indonesia today. Secondly, it deals with the query on how re-pilgrimage in Indonesia context in al-Qur’an’s perspective. This article concludes that re-pilgrimage in Indonesia served more on individual piety than the social one. In addition, there has been no verse indicated suggestion having re-pilgrimaged.